Dimensions of Intellectual Property Rights Law Regulations in Indonesia: Dimensions of Intellectual Property Rights Law Regulations in Indonesia - Anak Agung Sagung Ngurah Indradewi (Universitas Bali Dwipa, 2022)
Intellectual Property Rights are private rights where a creator/inventor is free to invite or not to apply for the registration of his intellectual works. That in Indonesia the existence of intellectual property rights as rights to immaterial objects or intangible objects. Property rights arise from a person's ability to produce a work based on the work of his brain/intellectuality, the results of that intellectual work then grow the concept of ownership of an intangible object in the form of intellectual property rights. Whereas intellectual property rights also recognize the existence of economic rights (economische) the community can take economic benefits from a copyrighted work of findings and or provide economic benefits that are positively useful in the community. The importance of understanding the Dimensions of Intellectual Property Rights Law in Indonesia, as a basis in implementing the protection of intellectual property rights in Indonesia (rechten/economic rights) in this case where the creators or inventors.